Activities Supporting the Awareness of Historical Background and Creating an Image of a Townk - Koštialová, Katarína (Lidé města, 2008)
Societies as well as individuals are members of some group or groups, observe similarities and differences, perceive time continuity and/or identify with the environment. What is more important, they can be emotionally linked to a cultural, ethnic, religious or other tradition or group. In contrast to rural existence, life in a town is socially and culturally much more differentiated; people participate in activities of various interest groups, clubs, religious or national organizations, cultural, sport or alternatively-oriented associations which, with their sub-cultural manifestations, participate more or less in activities of the town.